On the parametric analytics to investigate hole quality characteristics during helical milling of carbon fiber reinforced plastics stacks - Mehdi Tlija; Nimra Naeem; Mohammad Pervez Mughal; Kiran Mughal; Saad Ullah; Muhammad Sana; Anamta Khan (AIP Advances)
Dimensional inaccuracies are considered the primary challenge during the drilling of carbon fiber reinforced polymer materials to be employed in aeronautical applications. Helical milling is a beneficial machining process as compared to conventional drilling for making holes due to controlled cutting forces and tool movements that help in improving the hole quality. This work majorly emphasizes the effects of major process parameters like cutting speed, feed rate, tool coating, and eccentricity on the quality of machined holes for a quasi-isotropic layup of carbon fiber. For machining, a new strategy is employed by the inclusion of a 5 mm thick aluminum 2024 plate as a substrate to support the 10 mm thick workpiece of CFRP, thus eliminating the tool chattering and buckling of the workpiece and absorbing the heat generated during the machining process. Tool eccentricity, cutting speed, and tangential feed were input machining parameters while pitch was kept constant at 2 mm/rev. Analysis of variance is used to study the impact of input variables on the hole quality aspects that include delamination damage, length of uncut fiber, circularity error, and surface roughness by using the Taguchi design of experiment. Later, two and three step helical milling strategies were adopted in an attempt to accomplish aerospace quality holes without the need of reaming. The optimized parameters enabled machines to make H6 quality holes aiming to achieve the desired quality for aerospace. Signal-to-noise (S/N) ratio analysis was performed on response measures, and the least-is-best approach was chosen. It has been found that an improvement in the delamination factor at the exit is found at about 0.5%, and the surface roughness is about 73.84% when compared to the non-optimal settings of the data. These enhancements improve the overall structural integrity, assembly precision, and resistance to cyclic loading while ensuring better sealing and reduced wear. Reduction in the length of uncut fiber and delamination factor helps to improve the overall hole quality and durability.